La responsabilité sociale des entreprises dans l’industrie chinoise : une recomposition de la relation salariale ? - Clément Séhier (Revue de la Régulation)
This article offers an analysis of the movement of Corporate Social Responsibility (CSR) related to the transformations of the wage relationship in the Chinese industry. While important regulations supposed to organise the use of labour have been enacted since the 1990s, the weak collective rights granted to workers limit the possibility of compliance with the regulations. In this context of institutional blockage, the CSR movement can be interpreted as an attempt to develop a level of intermediate rules, from the company level. But so far, the private rules promoted by Multinational Corporations (MNCs) have been largely disconnected from the actors’ practices and do not contribute significantly to the stabilisation of the wage relationship. Based on a fieldwork, we show that the apparition of new actors in the field of CSR could herald a change in this movement. For instance, a procedural approach could be better assimilated by Chinese factories. Besides a compliance approach based on codes of conducts, some programs relying on experts or promoting workers’ participation are being developed. Eventually, the future of the role of CSR in the organization of the wage relationship remains open.